Li(x)@C(60): Calculations of the encapsulation energetics and thermodynamics - Slanina, Zdeněk; Uhlík, Filip; Lee, Shyi-Long; Adamowicz, Ludwik; Nagase, Shigeru (International journal of molecular sciences, 2008)
Li@C(60) and Li@C(70) can be prepared and thus, their calculations at higher levels of theory are also of interest. In the report, the computations are carried out on Li@C(60), Li(2)@C(60) and Li(3)@C(60) with the B3LYP density-functional theory treatment in the standard 3-21G and 6-31G* basis sets. The computed energetics suggests that Li(x) @C(60) species may be produced for a few small x values if the Li pressure is enhanced sufficiently. In order to check the suggestion, a deeper computational evaluation of the encapsulation thermodynamics is carried out.
Keywords: endohedral fullerenes; metallofullerene stabilities; calculated energetics and thermodynamics; computational optimization of syntheses; structure and bonding